Renewable Natural Resource Management and Use without Markets - Brown, Gardner M (Journal of Economic Literature, 2000)
Natural resources, by their nature, are not readily bent to the status of private property. Efficient resource use is complicated by jurisdictional externalities, public goods, non-use values, and beneficiaries spatially separated from the location of resources. The task is made more challenging by ecological complexity that obscures cause (benefits) and effects (costs), and dramatic time lags between individual actions and subsequent social consequences that, together with substantial uncertainty, introduce the chance of irreversibilities. Resource economists have played a major role in the literature on externalities, the development of individual transferable quotas, non-market valuation techniques and common property management.